2004
DOI: 10.1016/j.ijom.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of sagittal split advancement osteotomies with miniplates: a prospective, multicentre study with two-year follow-up

Abstract: Hof:Stabilisation of sagittal split advancement osteotomies with miniplates: a prospective, multicentre study with two-year follow-up Part I. Clinical parameters. Int.Abstract. The principal aim of this study was to assess the postoperative stability of bilateral sagittal split osteotomies (BSSO) using two miniplates. Part I reports on the clinical results including treatment characteristics, nerve functions, TMJ function, occlusional relapse and patient satisfaction.This prospective study evaluated a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In the short term, an increase in muscle and TMJ symptoms was normally found after mandibular advancement surgery, and this tended to decline over time, without being considered a risk factor for TMD 54 . On the other hand, it cannot be overlooked that there is also a risk of asymptomatic patients developing TMD after surgery 20,79,115,120,124,142 , and the condition of patients with TMJ symptoms worsening after surgery 12,103,108,142 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the short term, an increase in muscle and TMJ symptoms was normally found after mandibular advancement surgery, and this tended to decline over time, without being considered a risk factor for TMD 54 . On the other hand, it cannot be overlooked that there is also a risk of asymptomatic patients developing TMD after surgery 20,79,115,120,124,142 , and the condition of patients with TMJ symptoms worsening after surgery 12,103,108,142 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have concluded that SSRO of the mandible has a favorable effect on TMJ symptoms 20,31,55,120,141,142 , with better evolution for mandibular prognathism than mandibular retrognathism 141,142 . More specifically, De Clercq, et al 31 (1995) found significantly fewer post-operative TMJ symptoms in normal/low angle mandibular deficiency deformity, while there was no significant difference in the high angle group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BORSTLAP et al 6 reported a high plate removal rate of 55%, but only 7% of these were removed due to infection related reasons, and the authors therefore assume that the Removal of miniplates in BSSO patients 433 reason for the high removal frequency was an active policy of routine plate removal. In other studies, plate removal rates range from 7% to 16% 2,10,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Removals that were caused by platerelated complications were performed significantly sooner (a mean of 306 days postoperatively) than removals due to subjective discomfort (a mean of 608 days postoperatively). THEODOSSY et al 17 reported that plate removal was performed at a mean of 5.5 months (range 2-12 months) postoperatively, whereas BORS-TLAP et al 6 observed that all plates that needed removal were removed within 8 months postoperatively. In the present study, three patients had a follow-up time of less than 100 days and seven patients had a follow-up time of more than 100 days but less than 200 days.…”
Section: Discussionmentioning
confidence: 99%